2013
DOI: 10.1186/1866-1955-5-27
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of selected clinical problems in older adults with autism and intellectual disability

Abstract: BackgroundOriginally described as a disorder of childhood, evidence now demonstrates the lifelong nature of autism spectrum disorder (ASD). Despite the increase of the population over age 65, older adults with ASD remain a scarcely explored subpopulation. This study set out to investigate the prevalence of clinically relevant behaviors and medical problems in a sample of US adults aged 30 to 59 with ASD and intellectual disability (ID), in comparison to those with ID only.MethodsA cross-sectional study, with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 22 publications
1
43
0
Order By: Relevance
“…Recent investigations have found that up to sixty percent of adults with ASD and an intellectual disability present with difficult-to-manage behaviors, including self-injurious, disruptive, and destructive behaviors. [82]. In addition, a significant number of very young children present with difficult-to-manage behaviors, whereas oppositional and defiant behaviors can occur in children and adolescents [8386].…”
Section: Further Subtyping Asd Based On Co-occurring Symptoms Of Adhdmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent investigations have found that up to sixty percent of adults with ASD and an intellectual disability present with difficult-to-manage behaviors, including self-injurious, disruptive, and destructive behaviors. [82]. In addition, a significant number of very young children present with difficult-to-manage behaviors, whereas oppositional and defiant behaviors can occur in children and adolescents [8386].…”
Section: Further Subtyping Asd Based On Co-occurring Symptoms Of Adhdmentioning
confidence: 99%
“…With regard to the educational setting, cognitive ability and/or level of academic achievement, as well as severity of externalizing behavioral symptoms, may guide placements [119]. In comparison, adult-oriented treatment research may focus on subgroups of varying cognitive abilities or may focus on dividing groups according to adaptive behavior skills and the level of support required for managing day-to-day life [82, 120]. …”
Section: Treatment Research and Asd Subtypesmentioning
confidence: 99%
“…Autism spectrum disorder (ASD) is defined by the presence of characteristic behaviors present in early childhood [ 1 ]. While it is now recognized that ASD is typically a life-long condition, there exist only a handful of systematic studies of middle-aged and older adults [ 2 4 ]. According to the most recent estimate from the Centers for Disease Control (CDC), the prevalence of ASDs in US children is approximately 1.5 % [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] These conditions may lead to poorer well-being and impact on a person's ability to live independently. 18,19 Similarly, autistic people experience high levels of loneliness and isolation, which are associated with poorer cognitive function in older adults in the general population. [20][21][22] These factors independently or in conjunction may lead to an increased need for autistic people to transition to residential care in later life.…”
Section: Introductionmentioning
confidence: 99%